(untitled) - Silva, Anita Cristina Costa da; Lima, Luiz Antonio; Almeida, Willian Fernandes de; Thebaldi, Michael Silveira; Silva, Antônio Carlos da (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Tifton 85 production under deficit irrigation (2017)

(untitled)
Deficit irrigation consists of application of amounts of water less than plant requirements for satisfying water deficiencies of the crop, and this may maximize efficiency of water use. The aim of this study was to evaluate the effect of deficit irrigation on production of Tifton 85 grass. The experiment was carried out on the Santa Helena Farm in the municipality of Bom Despacho, MG, Brazil. Five levels of irrigation were used as treatments (28%, 42%, 57%, 71%, and 85% of the crop coefficient value) in randomized blocks with three replications. The following variables were evaluated: dry matter production (kg ha-1), leaf/stem ratio, height (cm), dead plant material (%), leaf area index, leaf area ratio (m2 kg-1), leaf weight ratio (kg kg-1), and specific leaf area (m2 kg-1). A difference was observed for Tifton 85 production in which the greatest average yield (6126.35 kg ha-1) was obtained through application of 71% Kc. For the other characteristics, there was no difference for any of the variables evaluated.